Methods of Analyzing Microsized Plastics in the Environment - Hyunjeong Woo (MDPI AG, 2021)
Microplastics are found in various environments with the increasing use of plastics worldwide. Several methods have been developed for the sampling, extraction, purification, identification, and quantification of microplastics in complex environmental matrices. This study intends to summarize recent research trends on the subject. Large microplastic particles can be sorted manually and identified through chemical analysis; however, sample preparation for small microplastic analysis is usually more difficult. Microplastics are identified by evaluating the physical and chemical properties of plastic particles separated through extraction and washing steps from a mixture of inorganic and organic particles. This identification has a high risk of producing false-positive and false-negative results in the analysis of small microplastics. Currently, a combination of physical (e.g., microscopy), chemical (e.g., spectroscopy), and thermal analyses is widely used. We aim to summarize the best strategies for microplastic analysis by comparing the strengths and limitations of each identification method.